Partyrpg: concepção e elaboração de uma plataforma de RPG para web - FORMENTO, Leonardo Santos (2020)
Important magazines and academic journals are bringing changes with relation a games, revealing it no more as something purity for entertainment, but also as a tool for educators to improve assimilation of contents and the learning of the students. Among these, the RPG stands out for being multidisciplinary and providing greater creative freedom for its participants, and greater socialization among them. Other benefits are also presented, such as a greater motivation for the proposed activity, for writing and the search for new knowledge. Based on these benefits, a web platform is proposed, named of PartyRPG, in the future can be used in a distance education programs (EAD). Then, based on the software engineer, was realized the platform planning, showing as final result three documents that exposes requirement specification, the analysis specific and the project model. As result, the development of a prototype, that being applied to users.